A preparation method of a double-doped porous carbon supported noble metal catalyst
Patent Information
- Application Number
- CN202610890400.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-09-01
AI Technical Summary
[0003]据检索,现有技术中已进行了一些双掺杂多孔碳的电催化材料的研究,方法主要集中在一些特殊形貌结构(MOF),或者存在各种杂质离子Fe、Ni等,会给后续催化剂或者膜电极带来一定的毒化作用
(1)双掺杂中,碘在高温条件下具有一定的对碳的腐蚀作用,可以对上述氧化镁模板导致的死孔进行联通,增强其后期对氧气的传质,提高催化剂的利用率。
Smart Images

Figure CN122677461A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalysis, specifically to a method for preparing a dual-doped porous carbon-supported noble metal catalyst. Background Technology
[0002] Energy shortages and environmental pollution have gradually become key constraints on socio-economic development. The rise of proton exchange membrane fuel cells (PEMFCs) and fuel cell power plants marks the arrival of the hydrogen energy era. PEMFCs directly convert the chemical energy of hydrogen and oxygen into electrical energy, and catalysts are essential in this process. In recent years, research on PEMFC catalysts has mainly focused on studying the morphology, size, and composition of platinum-based nanoparticles to improve catalyst activity and durability. However, research on catalyst supports, especially commercially viable mass-producible supports, is relatively limited. Traditional platinum-based catalysts use carbon supports that do not contain any dopants and do not possess catalytic activity themselves; their main function is to disperse platinum nanoparticles and maintain conductivity.
[0003] A search of existing technologies reveals some research on electrocatalytic materials using dual-doped porous carbon. These methods primarily focus on uniquely morphological structures (MOFs) or the presence of various impurity ions such as Fe and Ni, which can poison subsequent catalysts or membrane electrodes. Furthermore, no reports have been found on non-noble metal dual-doped, particularly nitrogen- and iodine-co-doped, porous carbon-supported noble metal catalysts. Enhancing the catalytic activity of the carbon support itself through dual doping, followed by loading with a noble metal catalyst, will help improve the catalyst's activity and stability. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing a dual-doped porous carbon-supported noble metal catalyst.
[0005] Conventional commercial porous carbon is unfavorable for nitrogen and iodine doping due to issues such as pore structure, pore connectivity, and the number of defect sites. Compared to other pore-forming agents and methods, this invention utilizes magnesium oxide particles to facilitate subsequent elemental doping, particularly iodine doping. However, templates like magnesium oxide and aluminum oxide can lead to dead pores (zinc oxide, compared to other pore-forming agents like aluminum oxide, exhibits metal volatilization at high temperatures, which to some extent helps create interconnected pores and reduce dead pores). Iodine doping, on the other hand, has a corrosive effect on carbon, which can connect the dead pores caused by the magnesium oxide template. The interaction between these two factors results in a better overall effect on both pore formation and doping. When loading noble metal catalysts, the interaction between the doped iodine and alcohol is crucial for the uniform dispersion of Pt nanoparticles.
[0006] The objective of this invention is achieved through the following technical solution: This invention provides a method for preparing a dual-doped porous carbon-supported noble metal catalyst, comprising the following steps: S1. Add the magnesium oxide nanoparticle dispersion dropwise to a water-soluble organic compound solution, stir, dry, and then calcine to obtain a solid powder; S2. Disperse the solid powder in an acid solution and heat it to obtain a porous carbon material; S3. Mix porous carbon material with nitrogen-containing organic matter and iodine, and then heat treat to obtain a double-doped porous carbon material. S4. A noble metal catalyst is supported on a porous carbon material to obtain a dual-doped porous carbon supported noble metal catalyst.
[0007] In one embodiment of the present invention, in the magnesium oxide nanoparticle dispersion of step S1, the ratio of magnesium oxide nanoparticles to dispersion solvent is 10-100g:50-1000mL. The dispersion solvent is anhydrous ethanol.
[0008] In one embodiment of the present invention, in step S1, the size of the magnesium oxide nanoparticles is 10-50 nm.
[0009] In one embodiment of the present invention, in the water-soluble organic compound solution of step S1, the ratio of water-soluble organic compound to solvent is 20-100g: 500-2000mL. The solvent is deionized water.
[0010] As one embodiment of the present invention, in step S1, the water-soluble organic compound includes one or more of starch, carboxymethyl cellulose, hydroxypropyl methyl cellulose, glucose, sucrose, citric acid, and polyethylene glycol.
[0011] In one embodiment of the present invention, in step S1, the dropping rate is 4–6 mL / min. The stirring speed is 100–400 rpm, and the time is 3–8 h. The drying temperature is 90–120 °C, and the time is 12–24 h.
[0012] In one embodiment of the present invention, in step S1, the mass ratio of magnesium oxide nanoparticles to water-soluble organic compound is 40-60:100.
[0013] In one embodiment of the present invention, in step S1, the particles are dried and then sieved to control the particle size to below 150 micrometers.
[0014] In one embodiment of the present invention, in step S1, the calcination temperature is 600-900℃, and the time is 1-5 hours. Calcination is carried out under an inert atmosphere. The calcination product is a mixture of carbon-coated magnesium oxide.
[0015] In one embodiment of the present invention, in step S2, the acid solution is a dilute nitric acid solution with a concentration of 0.1–1 M. The acid solution can remove magnesium oxide nanoparticles and perform weak oxidation and hydrophilic treatment on the carbon material, which is beneficial for subsequent doping.
[0016] In one embodiment of the present invention, in step S2, the temperature of the heat treatment is 40-90°C and the time is 1-5 hours.
[0017] In one embodiment of the present invention, in step S2, the solid powder after heat treatment is filtered, washed and dried to obtain a porous carbon material.
[0018] In one embodiment of the present invention, in step S3, the mass ratio of porous carbon material, nitrogen-containing organic matter, and elemental iodine is 1:4-6:1-5, preferably 1:5:1-5, and more preferably 1:5:1-2. The nitrogen-containing organic matter is 2-methylimidazole.
[0019] In one embodiment of the present invention, in step S3, the heat treatment temperature is 500–1100°C, and the time is 3–8 hours. The heat treatment is carried out in a high-temperature inert atmosphere.
[0020] As one embodiment of the present invention, in step S4, loading a noble metal catalyst onto a porous carbon material involves adding dual-doped porous carbon to a solution containing a noble metal precursor, stirring, adding a reducing agent, first purging with a special atmosphere, and then heating to react, thereby obtaining a dual-doped porous carbon-supported noble metal catalyst.
[0021] The ratio of the amount of dual-doped porous carbon to the solution containing noble metal precursor is 5g:80-120mL.
[0022] Stirring was performed at room temperature for 1–2 hours.
[0023] The ratio of dual-doped porous carbon to reducing agent is 5g:45-55mL. The reducing agent is ethanol.
[0024] The special atmosphere is CH4 and / or C2H4. The venting time is 30-60 min. CH4 and C2H4 are adsorbed on the surface of the noble metal particles, thereby inhibiting particle growth during heat treatment and maintaining the activity of the catalyst particles.
[0025] The heating reaction is carried out at a temperature of 75-85 ℃ for 2-4 h.
[0026] The product of the heated reaction was filtered, washed, and dried to obtain a dual-doped porous carbon-supported noble metal catalyst.
[0027] The obtained porous carbon-supported noble metal catalyst contains one or more of Pt, Pd, Au, Ru, Ir, PtRu, and PtPd, and the noble metal content accounts for 20% to 70% of the total mass of the catalyst.
[0028] The catalyst of this invention is a nitrogen and iodine dual-doped catalyst.
[0029] Nitrogen doping: Nitrogen doping can break the stable structure of sp2 carbon, providing more atomic-level catalytic active sites and defect sites, thereby improving the oxygen reduction catalytic activity of the catalyst. In addition, nitrogen doping is beneficial to the uniform dispersion of ionic polymers in the subsequent fuel cell catalyst slurry, thus improving mass transfer efficiency.
[0030] Iodine doping: On the one hand, iodine has a certain corrosive effect on carbon under high temperature conditions (the corrosive effect on graphitized carbon is relatively weak), which can connect the dead pores caused by the magnesium oxide template, enhance the mass transfer of oxygen in the later stage, and improve the utilization rate of the catalyst; on the other hand, iodine doping can further enhance the catalytic activity of the support itself. Through the interaction between iodine and alcohol, it can promote the uniform dispersion of noble metal Pt particles and improve the activity and durability of the catalyst.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) In the double doping, iodine has a certain corrosive effect on carbon under high temperature conditions, which can connect the dead pores caused by the magnesium oxide template, enhance the mass transfer of oxygen in the later stage, and improve the utilization rate of the catalyst.
[0032] (2) In dual doping, nitrogen and iodine can further enhance the catalytic activity of the support itself. Through the interaction between I and alcohol, they promote the uniform dispersion of noble metal Pt particles and improve the activity and durability of the catalyst. Other doping does not have the above effects. Attached Figure Description
[0033] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 TEM image of the dual-doped porous carbon support prepared in Example 1; Figure 2 TEM image of the catalyst prepared in Example 1; Figure 3 This is a TEM image of the catalyst prepared in Comparative Example 1. Detailed Implementation
[0034] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, providing detailed implementation methods and specific operating procedures, which will help those skilled in the art to further understand the present invention. It should be noted that the scope of protection of the present invention is not limited to the following embodiments; any adjustments and improvements made under the concept of the present invention are all within the scope of protection of the present invention.
[0035] This invention provides a method for preparing a dual-doped porous carbon-supported noble metal catalyst, comprising the following steps: Step 1: Add the water-soluble organic compound to deionized water and stir until completely dissolved to obtain solution A; Step 2: Weigh magnesium oxide nanoparticles and ultrasonically disperse them in anhydrous ethanol. Slowly add the dispersed particles to solution A while stirring. Continue stirring, then place the solution in a drying oven to dry and grind it to obtain solid powder B. Step 3: Treat solid powder B under an inert atmosphere at 600-900℃ to obtain solid powder C; then disperse solid powder C in dilute nitric acid solution, treat at 60℃, filter, wash and dry to obtain porous carbon material D; Step 4: Weigh 5g of porous carbon material D and mix it evenly with 2-methylimidazole and iodine. Then, heat-treat it in a high-temperature inert atmosphere to obtain double-doped porous carbon material E. Step 5: According to the stoichiometric ratio, add the dual-doped porous carbon to the solution containing the noble metal precursor and stir at room temperature; then add ethanol as a reducing agent, first purge with a special atmosphere, then raise the temperature to 80°C for reaction, and after filtration, washing and drying, obtain the dual-doped porous carbon supported noble metal catalyst.
[0036] Example 1 A method for preparing a dual-doped porous carbon-supported noble metal catalyst specifically includes the following steps: 1) Weigh 50g of sucrose and add it to 1000mL of deionized water. Stir for 30 minutes until completely dissolved to obtain solution A. 2) Weigh 100g of 10nm magnesium oxide nanoparticles and ultrasonically disperse them in 1000mL of anhydrous ethanol. Under stirring conditions, the stirring speed is 300rpm, and the ethanol is slowly added dropwise to solution A at a rate of 5mL / min. Continue stirring for 3h, and then place it in a drying oven at 120℃ for 12h. After grinding, pass it through a 100-mesh sieve to obtain solid powder B (particle size controlled below 150 micrometers). 3) Solid powder B was treated at 900℃ for 2 hours under an inert argon atmosphere to obtain solid powder C; then solid powder C was dispersed in 0.5M dilute nitric acid solution and treated at 60℃ for 2 hours. After filtration, washing and drying, porous carbon material D was obtained. 4) Weigh 5g of porous carbon material D and mix it with 2-methylimidazole and iodine in a weight ratio of 1:5:1. Then, heat-treat the mixture at 750℃ for 3 hours in a high-temperature inert atmosphere to obtain double-doped porous carbon material E. Its TEM image is shown below. Figure 1 As shown, the pore size of the double-doped porous carbon is approximately 10–15 nm. Figure 1 The middle circle is connected in a three-dimensional porous structure. 5) Add 5g of dual-doped porous carbon to 100mL of chloroplatinic acid solution with a concentration of 0.133g / mL, and stir for 1h at room temperature (25℃). Then add 50mL of ethanol as a reducing agent, purge with CH4 for 30min, and then raise the temperature to 80℃ for 3h. After filtration, washing, and drying, obtain the dual-doped porous carbon-supported platinum catalyst. TEM image of the prepared catalyst is shown below. Figure 2 As shown, platinum nanoparticles are uniformly distributed on a dual-doped porous carbon support, with an average particle size of 2 nm (obtained by averaging the dimensions of 100 nanoparticles in the figure).
[0037] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.386 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.386 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.685V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm, the voltage is 0.6(3s)-0.95V(3s). 2 The output voltage at the current density is 0.674V, with a decay of 11mV.
[0038] Example 2 A method for preparing a dual-doped porous carbon-supported noble metal catalyst specifically includes the following steps: 1) Weigh 50g of sucrose and add it to 1000mL of deionized water. Stir for 30 minutes until completely dissolved to obtain solution A. 2) Weigh 100g of 10nm magnesium oxide nanoparticles and ultrasonically disperse them in 1000mL of anhydrous ethanol. Under stirring conditions, the mixture is slowly added dropwise to solution A at a stirring speed of 300rpm and 5mL / min. Continue stirring for 3h, then place it in a drying oven at 120℃ and dry for 12h. After grinding, pass it through a 100-mesh sieve to obtain solid powder B (particle size controlled below 150μm). 3) Solid powder B was treated at 900℃ for 2 hours under an inert argon atmosphere to obtain solid powder C; then solid powder C was dispersed in 0.5M dilute nitric acid solution and treated at 60℃ for 2 hours. After filtration, washing and drying, porous carbon material D was obtained. 4) Weigh 5g of porous carbon material D and mix it with 2-methylimidazole and iodine in a weight ratio of 1:5:2. Then, heat-treat it at 750℃ for 3h in a high-temperature inert atmosphere to obtain double-doped porous carbon material E. 5) Add 5g of dual-doped porous carbon to 100mL of chloroplatinic acid solution with a concentration of 0.133g / mL, and stir for 1h at room temperature; then add 50mL of ethanol as a reducing agent, first purge with CH4 for 30min, then raise the temperature to 80℃ and react for 3h. After filtration, washing, and drying, obtain the dual-doped porous carbon-supported platinum catalyst. The prepared catalyst platinum nanoparticles are uniformly distributed on the dual-doped porous carbon support, with an average particle size of 2.5nm (the average value of the statistical dimensions of 100 nanoparticles in the figure).
[0039] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.375 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.375 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.680V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm, the voltage is 0.6(3s)-0.95V(3s). 2 The output voltage at the current density is 0.672V, with a decay of 8mV.
[0040] Example 3 A method for preparing a dual-doped porous carbon-supported noble metal catalyst specifically includes the following steps: 1) Weigh 50g of sucrose and add it to 1000mL of deionized water. Stir for 30 minutes until completely dissolved to obtain solution A. 2) Weigh 100g of 20nm magnesium oxide nanoparticles and ultrasonically disperse them in 1000mL of anhydrous ethanol. Under stirring conditions, the stirring speed is 300rpm, and the mixture is slowly added dropwise to solution A at a rate of 5mL / min. Continue stirring for 3h, then place it in a drying oven at 120℃ for 12h to dry, grind it, and then pass it through a 100-mesh sieve to obtain solid powder B (particle size controlled below 150 micrometers). 3) Solid powder B was treated at 900℃ for 2 hours under an inert argon atmosphere to obtain solid powder C; then solid powder C was dispersed in 0.5M dilute nitric acid solution and treated at 60℃ for 2 hours. After filtration, washing and drying, porous carbon material D was obtained. 4) Weigh 5g of porous carbon material D and mix it with 2-methylimidazole and iodine in a weight ratio of 1:5:1. Then, heat-treat it in a high-temperature inert atmosphere at 750℃ for 3 hours to obtain double-doped porous carbon material E. 5) Add 5g of dual-doped porous carbon to 100mL of chloroplatinic acid solution with a concentration of 0.133g / mL, and stir for 1h at room temperature; then add 50mL of ethanol as a reducing agent, first purge with CH4 for 30min, then raise the temperature to 80℃ and react for 3h. After filtration, washing, and drying, obtain the dual-doped porous carbon-supported platinum catalyst. The prepared catalyst shows that platinum nanoparticles are uniformly distributed on the dual-doped porous carbon support, with an average particle size of 2.2nm (the average value was obtained from the statistical size of 100 nanoparticles in the figure).
[0041] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.372 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.372 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.676V; according to the DOE test standard, after 30,000 accelerated durability tests from 0.6 (3s) to 0.95V (3s), at 2A / cm 2 The output voltage at the current density is 0.663V, with a decay of 13mV.
[0042] Example 4 A method for preparing a dual-doped porous carbon-supported noble metal catalyst specifically includes the following steps: 1) Weigh 50g of sucrose and add it to 1000mL of deionized water. Stir for 30 minutes until completely dissolved to obtain solution A. 2) Weigh 100g of 50nm magnesium oxide nanoparticles and ultrasonically disperse them in 1000mL of anhydrous ethanol. Under stirring conditions, the stirring speed is 300rpm, and the mixture is slowly added dropwise to solution A at a rate of 5mL / min. Continue stirring for 3h, and then place it in a drying oven at 120℃ to dry for 12h. After grinding, pass it through a 100-mesh sieve to obtain solid powder B (particle size controlled below 150 micrometers). 3) Solid powder B was treated at 900℃ for 2 hours under an inert argon atmosphere to obtain solid powder C; then solid powder C was dispersed in 0.5M dilute nitric acid solution and treated at 60℃ for 2 hours. After filtration, washing and drying, porous carbon material D was obtained. 4) Weigh 5g of porous carbon material D and mix it with 2-methylimidazole and iodine in a weight ratio of 1:5:1. Then, heat-treat it in a high-temperature inert atmosphere at 750℃ for 3 hours to obtain double-doped porous carbon material E. 5) Add 5g of dual-doped porous carbon to 100mL of chloroplatinic acid solution with a concentration of 0.133g / mL, and stir for 1h at room temperature; then add 50mL of ethanol as a reducing agent, first purge with CH4 for 30min, then raise the temperature to 80℃ and react for 3h. After filtration, washing, and drying, obtain the dual-doped porous carbon-supported platinum catalyst. The prepared catalyst shows that platinum nanoparticles are uniformly distributed on the dual-doped porous carbon support, with an average particle size of 2.3nm (the average value was obtained from the statistical size analysis of 100 nanoparticles in the figure).
[0043] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.369 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.369 A / mg Pt@0.9V. 2The output voltage at the current density is 0.675V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm², the voltage is 0.675V-0.95V(3s). 2 The output voltage at the current density is 0.664V, with a decay of 11mV.
[0044] Example 5 A method for preparing a dual-doped porous carbon-supported noble metal catalyst specifically includes the following steps: 1) Weigh 50g of sucrose and add it to 1000mL of deionized water. Stir for 30 minutes until completely dissolved to obtain solution A. 2) Weigh 100g of 10 nm magnesium oxide nanoparticles and ultrasonically disperse them in 1000mL of anhydrous ethanol. Under stirring conditions, the stirring speed is 300rpm, and the mixture is slowly added dropwise to solution A at a rate of 5mL / min. Continue stirring for 3h, and then place it in a drying oven at 120℃ for 12h. After grinding, pass it through a 100-mesh sieve to obtain solid powder B (particle size controlled below 150 micrometers). 3) Solid powder B was treated at 800℃ for 2 hours under an inert argon atmosphere to obtain solid powder C; then solid powder C was dispersed in 0.1M dilute nitric acid solution and treated at 60℃ for 2 hours. After filtration, washing and drying, porous carbon material D was obtained. 4) Weigh 5g of porous carbon material D and mix it with 2-methylimidazole and iodine in a weight ratio of 1:5:1. Then, heat-treat it in a high-temperature inert atmosphere at 750℃ for 3 hours to obtain double-doped porous carbon material E. 5) Add 5g of dual-doped porous carbon to 100mL of chloroauric acid solution with a concentration of 0.133g / mL, and stir for 1h at room temperature; then add 50mL of ethanol as a reducing agent, first purge with CH4 for 30min, then raise the temperature to 80℃ and react for 3h. After filtration, washing, and drying, obtain the dual-doped porous carbon-supported platinum catalyst. The prepared catalyst shows that platinum nanoparticles are uniformly distributed on the dual-doped porous carbon support, with an average particle size of 2.1nm (the average value of 100 nanoparticles in the figure is used).
[0045] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.378 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.378 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.683V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm², the voltage is 0.683V-0.95V(3s). 2 The output voltage at the current density is 0.673V, with a decay of 10mV.
[0046] Comparative Example 1 The only difference between this comparative example and Example 1 is that magnesium oxide is not added in step 2; all other operations are exactly the same.
[0047] TEM image of the prepared catalyst is as follows Figure 3 As shown, the platinum nanoparticles are unevenly distributed on the carbon support, and the average size of the platinum particles is significantly increased to 4.5 nm.
[0048] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.312 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.312 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.663V; according to the DOE test standard, after 30,000 accelerated endurance tests from 0.6 (3s) to 0.95V (3s), the output voltage at a current density of 2A / cm2 is 0.642V, with a decay of 21mV.
[0049] Comparative Example 2 The only difference between this comparative example and Example 1 is that magnesium oxide with a size of 150 nm was added in step 2; all other operations were identical. The platinum nanoparticles were more uniformly distributed on the carbon support, and the average size of the platinum particles increased significantly to 3.5 nm.
[0050] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.334 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.334 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.670V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm, the voltage is 0.6(3s)-0.95V(3s). 2 The output voltage at the current density is 0.652V, with a decay of 18mV.
[0051] Comparative Example 3 The only difference between this comparative example and Example 1 is that the dopant element I is replaced with S.
[0052] Since sulfur doping does not corrode carbon, it cannot achieve the purpose of connecting dead pores. As a result, the platinum nanoparticles of the prepared catalyst are unevenly distributed on the carbon support, and the average size of the platinum particles is significantly increased to 5.5 nm.
[0053] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.289 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.289 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.653V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm², the voltage is 0.653V-0.95V-3s. 2 The output voltage at the current density is 0.634V, with a decay of 19mV.
[0054] Comparative Example 4 The only difference between this comparative example and Example 1 is that element I is replaced with compound NH4I.
[0055] Because the decomposition temperature of NH4I is low, it cannot achieve the purpose of doping. The platinum nanoparticles of the prepared catalyst are unevenly distributed on the carbon support, and the average size of the platinum particles is significantly increased to 5.7 nm.
[0056] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.269 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.269 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.647V; according to the DOE test standard, after 30,000 accelerated durability tests at 2A / cm, the voltage is 0.6(3s)-0.95V(3s). 2 The output voltage at the current density is 0.624V, with a decay of 23mV.
[0057] Comparative Example 5 The only difference between this comparative example and Example 1 is that the iodine doping is removed, and only nitrogen-doped organic matter is used.
[0058] Since sulfur doping does not corrode carbon, it cannot achieve the purpose of connecting dead pores. As a result, the platinum nanoparticles of the prepared catalyst are unevenly distributed on the carbon support, and the average size of the platinum particles is significantly increased to 5.8 nm.
[0059] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.265 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.265 A / mg Pt@0.9V. 2The output voltage at the current density is 0.645V; according to the DOE test standard, after 30,000 accelerated durability tests from 0.6 (3s) to 0.95V (3s), at 2A / cm 2 The output voltage at the current density is 0.631V, with a decay of 14mV.
[0060] Comparative Example 6 The only difference between this comparative example and Example 1 is that the nitrogen-doped organic matter is removed, and only iodine doping is performed.
[0061] The platinum nanoparticles of the prepared catalyst are relatively uniformly distributed on the carbon support, and the average size of the platinum particles is significantly increased to 3.4 nm.
[0062] Activity, performance, and durability testing: The above catalyst was prepared into a 25cm... 2 The membrane electrode was subjected to planned performance testing, with a cathode Pt loading of 0.3 mg / cm³. 2 The Pt loading at the anode is 0.05 mg / cm³. 2 The test temperature was 80℃. Under H2 / O2 conditions, the anode-cathode stoichiometry ratio was 9.5 / 2, the back pressure was 50 kPa, and the relative humidity was 100% RH. The measured catalyst specific activity was 0.353 A / mg Pt@0.9V. Under H2 / Air conditions, the anode-cathode stoichiometry ratio was 1.8 / 1.5, the back pressure was 50 kPa, and the relative humidity was 100% RH. The catalyst specific activity was 0.353 A / mg Pt@0.9V. 2 The output voltage at the current density is 0.671V; according to the DOE test standard, after 30,000 accelerated endurance tests from 0.6 (3s) to 0.95V (3s), the output voltage at a current density of 2A / cm2 is 0.658V, with a decay of 13mV.
[0063] The same performance test was conducted on the examples and comparative examples, and the results are shown in Table 1 below: Table 1
[0064] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a double-doped porous carbon supported noble metal catalyst, characterized in that, Includes the following steps: S1. Add the magnesium oxide nanoparticle dispersion dropwise to a water-soluble organic compound solution, stir, dry, and then calcine to obtain a solid powder; S2. Disperse the solid powder in an acid solution and heat it to obtain a porous carbon material; S3. Mix porous carbon material with nitrogen-containing organic matter and iodine, and then heat treat to obtain a double-doped porous carbon material. S4. A noble metal catalyst is supported on a porous carbon material to obtain a dual-doped porous carbon supported noble metal catalyst.
2. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In the magnesium oxide nanoparticle dispersion of step S1, the ratio of magnesium oxide nanoparticles to dispersion solvent is 10-100g: 50-1000mL. And / or, in step S1, the size of the magnesium oxide nanoparticles is 10–50 nm.
3. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S1, the ratio of water-soluble organic compound to solvent in the solution is 20-100g: 500-2000mL. And / or, in step S1, the water-soluble organic compound includes one or more of starch, carboxymethyl cellulose, hydroxypropyl methyl cellulose, glucose, sucrose, citric acid, and polyethylene glycol.
4. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S1, the dropping rate is 4-6 mL / min; And / or, in step S1, the stirring speed is 100-400 rpm and the time is 3-8 h; And / or, in step S1, the drying temperature is 90–120°C and the time is 12–24 h; And / or, in step S1, the calcination temperature is 600-900℃ and the time is 1-5h.
5. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S2, the acid solution is a dilute nitric acid solution with a concentration of 0.1–1 M.
6. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S2, the heating temperature is 40–90°C and the time is 1–5 hours.
7. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S3, the mass ratio of porous carbon material, nitrogen-containing organic matter, and elemental iodine is 1:4-6:1-5; And / or, in step S3, the nitrogen-containing organic compound is 2-methylimidazole.
8. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S3, the heat treatment temperature is 500–1100℃ and the time is 3–8 hours.
9. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 1, characterized in that, In step S4, loading a noble metal catalyst onto a porous carbon material involves adding dual-doped porous carbon to a solution containing a noble metal precursor, stirring, adding a reducing agent, first purging with a special atmosphere, and then heating to react, thereby obtaining a dual-doped porous carbon-supported noble metal catalyst.
10. The method for preparing the dual-doped porous carbon-supported noble metal catalyst according to claim 9, characterized in that, The ratio of the amount of dual-doped porous carbon to the solution containing noble metal precursor is 5g:80-120mL; And / or, stirring is performed at room temperature for 1–2 hours; And / or, the ratio of dual-doped porous carbon to reducing agent is 5g:45-55mL; And / or, the reducing agent is ethanol; And / or, the special atmosphere is CH4 or C2H4; And / or, the reaction is heated to a temperature of 75-85 °C for 2-4 h; And / or, the noble metal in the obtained porous carbon-supported noble metal catalyst is one or more of Pt, Pd, Au, Ru, Ir, PtRu, and PtPd, and the noble metal content accounts for 20% to 70% of the total mass of the catalyst.